Uniformity Control of Laser-Induced Periodic Surface Structures - Huang, Ji; Liu, Yang; Jin, Sunjun; Wang, Zhipeng; Qi, Yaping; Zhang, Jian; Wang, Kun; Qiu, Rui (Frontiers in Physics, 2022)
Laser-induced periodic surface structures (LIPSS) are a universal phenomenon that can be observed on a variety of materials, including metals, semiconductors, and dielectrics, upon irradiation with ultrafast laser pulses. It has found various potential applications in the fields of optics, biologics, and mechatronics due to the efficient and flexible fabrication process and subwavelength quasi-periodic property. However, LIPSS face the challenge of uniformity control because the formation of micro-/nanostructures induced by ultrafast laser is a complex process involving multiple interacting factors, including laser energy deposition, phase change, light scattering, instantaneous local changes of material properties and their feedback mechanisms. Recently, there are some significant progresses regarding the control of LIPSS uniformity. In this work, we review recent experimental and methodological advances on this topic from three aspects: (1) laser-induced modified-LIPSS; (2) feedback mechanism of LIPSS formation; and (3) ultrafast laser pulse shaping. This review can stimulate the further investigations on uniformity control of LIPSS to support and accelerate the industrial applications of uniform LIPSS structures.